2023
DOI: 10.1002/cey2.328
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic regulation of hydrophobicity and basicity for copper hydroxide‐derived copper to promote the CO2 electroreduction reaction

Abstract: A simple method was proposed to activate alkaline Cu(OH) 2 with an acidic ionomer, Nafion, to regulate its surface microenvironment, including hydrophobicity and local basicity. In particular, the direct complete neutralization reaction between Cu(OH) 2 and Nafion in aqueous solution induces the exposing of vast anions which can exclude the in-situ-formed hydroxides and raise the local basicity. Remarkably, the optimal Nafionactivated Cu(OH) 2 -derived Cu can efficiently suppress the hydrogen evolution reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The diffraction peak located at 53°can be attributed to the Cu(OH) 2 (PDF#80-0656) nanowires asgrown on the CuFo substrate. 21,22 For CuFo-Cu@C/Au NWs, CuFo-Cu@C NWs without Au nanoparticles (SEM in Fig. S5 †) and CuFo-Cu/Au without the protective carbon layer (SEM in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peak located at 53°can be attributed to the Cu(OH) 2 (PDF#80-0656) nanowires asgrown on the CuFo substrate. 21,22 For CuFo-Cu@C/Au NWs, CuFo-Cu@C NWs without Au nanoparticles (SEM in Fig. S5 †) and CuFo-Cu/Au without the protective carbon layer (SEM in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of hydrophobic surface is an effective strategy to change the local microenvironment of the catalysts to promote CO 2 mass transfer and inhibit HER. Polymers, , ionic polymers, and organic molecules , that containing −CH 2 – or −CF 2 - mainchains can help increase the hydrophobicity of surface for promoting the local concentrations of CO 2 . Moreover, the surface hydrophobicity is closely related to the formation of •OH radicals, a strong oxidant formed in HCO 3 – electrolyte, that favors the fast reoxidation of Cu 0 to Cu δ+ (0 < δ < 2) species for strengthening the cooperation of Cu 0 and Cu δ+ …”
Section: Introductionmentioning
confidence: 99%
“…In particular, increasing the hydrophobicity of organic binder coatings can enhance the local OH − concentration and CO 2 /H 2 O concentration ratio, which contributes to improved selectivity. [10][11][12] In another example, a double layer of both anion-and cationconducting ionomers was introduced on the Cu surface to regulate the water concentration and to increase local pH by trapping hydroxide ions (OH − ), which resulted in significant suppression of the hydrogen evolution reaction (HER) and a record high 90% Faradaic efficiency of C 2+ products. [13] Alongside product selectivity, the poor long-term durability of Cu-based catalysts introduces another significant barrier to sustainable generation of C 2+ products from CO 2 R. Indeed, bare Cubased catalysts have been shown to be unstable when subjected to continuous CO 2 electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although various inorganic or organic coatings have been explored to enhance both the C 2+ product selectivity and stability of Cu-based catalysts, [11,15] understanding the impact of the most widely used binder-Nafion-is only now emerging. [12,[16][17][18][19][20][21][22][23] Recently, we reported that the activity, selectivity, and stability of CO 2 R can be drastically impacted by engineering the internal structure and properties of Nafion ionomer coatings on oxidederived Cu catalysts supported on carbon paper. [24] Importantly, thin layers of Nafion can beneficially stabilize the catalyst and create favorable microenvironments for CO 2 R, but can also lead to the blocking of active sites or introduce undesired mass transport limitations.…”
Section: Introductionmentioning
confidence: 99%